Branching fraction measurement of B̄0→D(*)+π- and B-→D(*)0π- and isospin analysis of B̄→D(*)π decays - Aubert, B; Barate, R; Bona, M; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges, E; Palano, A; et al. (2007)
Using 65×106 Υ(4S)→BB̄ events collected with the BABAR detector at the PEP-II e+e- storage ring at the Stanford Linear Accelerator Center, we measure the color-favored branching fractions B(B̄0→D+π- )=(2.55±0.05±0.16)×10-3, B(B̄0→D*+π-)=(2. 79±0.08±0.17)×10-3, B(B-→D0π-)=(4.90±0. 07±0.22)×10-3 and B(B-→D*0π-)=(5.52±0. 17±0.42)×10-3, where the first error is statistical and the second is systematic. With these results and the current world average for the branching fraction for the color-suppressed decay B̄0→D(*) 0π0, the cosines of the strong phase difference δ between the I=1/2 and I=3/2 isospin amplitudes are determined to be cos δ=0.872-0.007-0.029+0. 008+0.031 for the B̄→Dπ process and cos δ=0.924-0.017-0. 054+0.019+0.063 for the B̄→D*π process. Under the isospin symmetry, the results for cos δ suggest the presence of final-state interactions in the Dπ system. © 2007 The American Physical Society.